2022
DOI: 10.1038/s41598-022-11847-9
|View full text |Cite
|
Sign up to set email alerts
|

Human-to-dog transmission of SARS-CoV-2, Colombia

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of the current COVID-19 pandemic, has evolved to have a wide range of hosts, including non-human primates, wild and domestic animals. The ACE2 protein has a high level of conservation and is the common receptor invertebrate species for a viral infection to occur; this receptor could give rise to anthroponotic events. This article describes the first event of symptomatic transmission in Latin America from a human to a dog by the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…In Rio de Janeiro, 9 in 29 dogs (31%) tested positive through nasopharyngeal samples taken from 11 to 51 days after the human index COVID-19 case onset of symptoms, developing non-relevant clinical signs and mild respiratory and gastrointestinal manifestations, with no associated laboratory abnormalities [ 78 ]. In Colombia, Rivero et al [ 79 ] described the first event of symptomatic transmission in Latin America from a human to a dog by the B.1.625 lineage of SARS-CoV-2, finding 21 shared mutations in the complete genomes of viral sequences from owners and dogs. Therefore, the authors suggest that close contact between SARS-CoV-2-infected humans and pets should be avoided or limited to prevent the eventual emergence of novel mutations also dangerous to public health.…”
Section: Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…In Rio de Janeiro, 9 in 29 dogs (31%) tested positive through nasopharyngeal samples taken from 11 to 51 days after the human index COVID-19 case onset of symptoms, developing non-relevant clinical signs and mild respiratory and gastrointestinal manifestations, with no associated laboratory abnormalities [ 78 ]. In Colombia, Rivero et al [ 79 ] described the first event of symptomatic transmission in Latin America from a human to a dog by the B.1.625 lineage of SARS-CoV-2, finding 21 shared mutations in the complete genomes of viral sequences from owners and dogs. Therefore, the authors suggest that close contact between SARS-CoV-2-infected humans and pets should be avoided or limited to prevent the eventual emergence of novel mutations also dangerous to public health.…”
Section: Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…Among these 42 lineages, 15 were subjected to monitoring by regional health authorities and/or were reported as “escape variants” in the literature 27 – 36 ; 13 reached a prevalence of 1% or above in at least one or more countries, and 3 reached a global prevalence of 5% or above worldwide (B.1.177, B.1.160 and B.1.2). Two further lineages were reported to be associated with zoonotic transmission of SARS-CoV-2 to non human hosts 37 , 38 . Finally a total of 8 lineages were associated with a score greater than the cut-off for prioritization only in the interval of time that pre-dates the emergence of the Alpha and Beta VOC (Supplementary Data 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, though CanPV is circulating in the US, we do not know its host(s) in the region. It has been shown that in household settings when humans have virus infections (like SARS-CoV-2 and monkeypox virus) they often transmit these to their dogs 32, 33, 34, 35 . We do not know if the reverse happens with CanPV.…”
Section: Discussionmentioning
confidence: 99%